The Rayleigh-Ritz minimax formula in Kaplansky-Hilbert modules - GÖNÜLLÜ, UĞUR (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2015)
We give the RayleighRitz minimax formula for cyclically compact operators on KaplanskyHilbert modules.
Keywords: Kaplansky-Hilbert module; Cyclically compact operator; The Rayleigh-Ritz minimax formula